Electronic Presence System Using Biometric Images - Rakhman, Arkham Zahri; Yunmar, Rajif Agung; Budiman, Ega (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Conventional presence system have many limitation, in between difficulties in recording data that can have impact on the controlling from lecturer. In the other conventional presence systems are often fraudulent. This research purpose to design and developing electronic presence system in class room that are effective and efficient. In this research we are use biometric fingerprint sensor. There are several stages in this research. The first stage is the needs analysis to explore data and information and then formulate solutions to existing problems. The second stage is system design which includes system architecture design, system workflow design, data flow design, and database design. The third stage is the implementation of the system using programming languages and database software that is applied to microcomputers. The fourth stage is testing the system using black box testing. The last stage of this system development research is evaluation. This research took a case study at the Institut Teknologi Sumatera (ITERA).